Psychological adjustment of children and adolescents in residential care with Collaborating Families: A multi-informant assessment - Molano, Nuria; Espinosa, Elizabeth; León, Esperanza (Anales de Psicología / Annals of Psychology, 2024)
In residential care, programs such as Collaborating Families have been developed so that children and adolescents can experience periods of cohabitation in a positive family environment, which generates benefits for them and complements their residential care. The present study used the Strengths and Difficulties Questionnaire (SDQ) to study the psychological adjustment of 37 children and adolescents in residential care with collaborating families, comparing the assessments of 185 informants: the children themselves, their collaborating families, their caregivers at the protection center, as well as a comparison group of peers without collaborating families and their caregivers. In addition, this study analyzed whether the psychological adjustment of these children is related to some of their personal variables and their experience in family collaboration. The results showed significant differences between the psychological adjustment assessed by the different informants. Also, children with collaborating families tended to present a better psychological adjustment compared to the comparison group, with considerable effect sizes. Moreover, significant relationships were found between psychological adjustment and the children’s ratings about their family collaboration. Finally, some practical implications for the development of the program are discussed.